Pengaruh Game Edukasi Wordwall Maze Chase Terhadap Minat Belajar IPAS Peserta Didik Madrasah Ibtidaiyah - Nisa, Rofiatun; Rohmah, Annisa Nidaur (Limas PGMI, 2024)
This research aims to analyze and influence of the educational game Wordwall Maze Chase on interest in learning science for class V students at Madrasah Ibtidaiyah in Lamongan Regency. This research is quantitative research with a research design using Experiment and Control classes. The places for this research were 10 Madrasahs in Lamongan. The number of respondents was 181 Experiment clasess and 181 Control classes. Data collection methods used questionnaires and observation. Data analysis techniques use descriptive analysis and hypothesis testing. The research results show that the attractiveness of the wordwall maze chase educational game is in the medium category at 74.7%. Based on the comparison of the classification of learning interests of experimental class students who are in the medium category and those in the control class who are still in low classification, it proves that the application of the wordwall maze chase educational game can increase students' interest in learning. Based on the results obtained tcount>ttable (6.021>1.662), it can be concluded that the wordwall maze chase educational game has a significant effect on the learning interest of class V students in the science subject.